Dopaminergic amacrine cell number, plexus density, and dopamine content in the mouse retina: Strain differences and effects of Bax gene disruption. (December 2018) - Sankaran, Mathangi; Keeley, Patrick W.; He, Li; Iuvone, P. Michael; Reese, Benjamin E.
Abstract: Many types of retinal neuron modulate the distribution of their processes to ensure a uniform coverage of the retinal surface. Dendritic field area, for instance, is inversely related to the variation in cellular density for many cell types, observed either across retinal eccentricity or between different strains of mice that differ in cell number. Dopaminergic amacrine (DA) cells, by contrast, have dendritic arbors that bear no spatial relationship to the presence of their immediate homotypic neighbors, yet it remains to be determined whether their coverage upon the retina, as a population, is conserved across variation in their total number. The present study assessed the overall density of the dopaminergic plexus in the inner plexiform layer in the presence of large variation in the total number of DA cells, as well as their retinal dopamine content, to determine whether either of these features is conserved. We first compared these traits between two strains of mice (C57BL/6J and A/J) that exhibit a two-fold difference in DA cell number. We subsequently examined these same traits in littermate mice for which the pro-apoptotic Bax gene was either intact or knocked out, yielding a five-fold difference in DA cell number. In both comparisons, we found greater plexus density and DA content in the strain or condition with the greater number of DA cells. The population of DA cells, therefore, does not appear to self-regulate its process coverage to achieve a constant density as the DA mosaic is established during development, nor its functional dopamine content in maturity. Highlights: DA amacrine cell number varies considerably between different strains of mice. The density of DA processes is significantly greater in retinas with more DA cells. DA content is also significantly greater in retinas with more DA cells. Neither DA process outgrowth nor DA content is regulated at the population level.